Elementos para volver a pensar lo comunal: nuevas formas de acceso a la tierra y presión sobre el recurso en las comunidades campesinas de Colán y Catacaos - Burneo, María Luisa (2013)
This article argues that there is a transformation in the relationship between land, peasant communities and its members or comuneros. In the case of the communities of the Peruvian northern coast, this transformation links with a double dynamic: (i) the increasing external pressure on the resource from the private-national and transnational capitals, and (ii) the emergence of new means and motivations of access to land among the communal members. Under these circumstances, the communities seek to develop mechanisms of containment that, nevertheless, escape to their own logics of controland imply the risk of a progressive division of shares of the communal territory.In order to demonstrate this, the article examines new uses (and potential uses) of the land that generates more expectations among the comuneros, and new strategies of access to the resource that different actors compete for. Two peasant communities in the north coast of Peru, San Lucas de Colán and San Juan Bautista de Catacaos, are used as case studies. In orther to understand the variation of access to land trought time and to point out the new logics in the last decades, this article will examine the history and configuration process of land tenure in these communities. Finally, the article suggests as a hipothesis that these new logics transform the meanning of community and the relationship between the peasant communities and the comuneros. The latter seek to gain access tonew lands without necesarily involving their permanency in the communal territory nor having a productive use of their plots. Hence, the north coast communities are facing the challenge of a possible transformation in their functions like the control and defense of land.